2013
DOI: 10.1097/brs.0b013e31828826dd
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Teriparatide and Bisphosphonate Treatment to Reduce Pedicle Screw Loosening After Lumbar Spinal Fusion Surgery in Postmenopausal Women With Osteoporosis From a Bone Quality Perspective

Abstract: Our findings suggest that administration of teriparatide increased the quality of the lumbar spine bone marrow and pedicle cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
206
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(215 citation statements)
references
References 27 publications
8
206
1
Order By: Relevance
“…7,14 To avoid these postoperative complications, it may be necessary to implement some augmentation, such as use of a supplemental hook system or sublaminar cables combined with standard short segment PSF, 24 together with treatment of osteoporosis, for example, using parathyroid hormone (PTH). 16 This study had certain limitations. First, patients in this series were elderly, and it was impossible to follow 11 of 30 patients because 9 patients died of other diseases and 2 patients could not visit our hospital postoperatively due to excessive travel distance and/or physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…7,14 To avoid these postoperative complications, it may be necessary to implement some augmentation, such as use of a supplemental hook system or sublaminar cables combined with standard short segment PSF, 24 together with treatment of osteoporosis, for example, using parathyroid hormone (PTH). 16 This study had certain limitations. First, patients in this series were elderly, and it was impossible to follow 11 of 30 patients because 9 patients died of other diseases and 2 patients could not visit our hospital postoperatively due to excessive travel distance and/or physical disability.…”
Section: Discussionmentioning
confidence: 99%
“…In previous clinical series, sacroiliac screw loosening was approximately 10% in mixed populations [31,32]. As known from spine surgery, the risk of screw loosening in patients with osteoporosis can be as much as 25% [30,47]. Thus, the presence of osteoporosis was estimated to double the rate of screw loosening, therefore we set the clinically relevant effect size in this model of osteoporosis as cement resulting in halving of the amount of screw migration.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with osteoporotic bone, however, loosening of the screws frequently is seen [15,30,47]. This is a dynamic process and failure to achieve stable anchorage in sacroiliac screw fixation can result in loosening of the screws, but equally important can be the long-lasting immobilization resulting from pain in patients who are already-frail and deconditioned.…”
Section: Introductionmentioning
confidence: 99%
“…14,26,28,44 We previously reported that teriparatide administered daily for 2 months before surgery reduced the incidence of pedicle screw loosening after instrumented lumbar fusion in postmenopausal women with osteoporosis, suggesting that teriparatide increased not only bone mass, but also the quality of the pedicle cortex. 34 However, a clinical study of the effect of teriparatide on pedicle screw insertional torque in postmenopausal women with osteoporosis has not yet been reported. The purpose of the current prospective study was to examine the efficacy of preoperative teriparatide for affecting insertional torque of pedicle screws investigated during fusion surgery in postmenopausal women with osteoporosis.…”
mentioning
confidence: 99%